Comprehensive review on divisible load theory: concepts, strategies, and approaches - Ghanbari, Shamsollah; Othman, Mohamed (Hindawi Publishing Corporation, 2014)
There is extensive literature concerning the divisible load theory. The divisible load theory is mainly applied for scheduling in the area of distributed computing. It is based on the fact that the load can be divided into some arbitrarily independent parts, in which each part can be processed independently by a processor. This paper reviews the literature concerning the divisible load theory, while focusing on the details of the basic concepts, approaches, strategies, typologies, and open problems.